Developmental Nuclear Localization and Quantification of GFP-Tagged EB1c in Arabidopsis Root Using Light-Sheet Microscopy - Novák, Dominik; Kuchařová, Anna; Ovečka, Miroslav; Komis, George; Šamaj, Jozef (Frontiers in Plant Science, 2016)
The development of the root apex is determined by progress of cells from the meristematic region to the successive post-mitotic developmental zones for transition, cell elongation and final cell differentiation. We addressed root development, tissue architecture and root developmental zonation by means of light-sheet microscopic imaging of Arabidopsis thaliana seedlings expressing END BINDING protein 1c (EB1c) fused to green fluorescent protein (GFP) under control of native EB1c promoter. Unlike the other two members of the EB1 family, plant-specific EB1c shows prominent nuclear localization in non-dividing cells in all developmental zones of the root apex. The nuclear localization of EB1c was previously mentioned solely in meristematic cells, but not further addressed. With the help of advanced light-sheet microscopy, we report quantitative evaluations of developmentally-regulated nuclear levels of the EB1c protein tagged with GFP relatively to the nuclear size in diverse root tissues (epidermis, cortex and endodermis) and root developmental zones (meristem, transition and elongation zones). Our results demonstrate a high potential of light-sheet microscopy for 4D live imaging of fluorescently-labelled nuclei in complex samples such as developing roots, showing capacity to quantify parameters at deeper cell layers (e.g. endodermis) with minimal aberrations. The data presented herein further signify the unique role of developmental cell reprogramming in the transition from cell proliferation to cell differentiation in developing root apex.